REFERENSI ARTIKEL JURNAL IKATAN PUSTAKAWAN INDONESIA (IPI) PERIODE 2018-2021 - ROCHANI NANI RAHAYU; SAIFUL ANWAR (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2022)
A citation analysis was carried out on the 2018-2021 Jurnal Ikatan Pustakawan Indonesis to find out which articles were published, the references used, the types of references, and the year of publication of references from within and outside the country. The data source is downloaded from https://jurnal.ipi.web.id/jurnalipi the data is recordedaccording to the research objetives, then grouped according to the type of document and the range of year of publication.The data is prcesessed using MicrosofrExcel 2010, and the result show that there are 433 domestic documents used, the mostly wideyused are in the 2018-2019 range, (94 titles; 21.99%), the second places is in 2015-2018 and 2012-2014 with 74 titles (17,09%), third place in 2009 – 2011 with 50 titles (11.54%).used books (170 titles;39.26%), jurnals in second place,130 titles (30.26%) the third place is are websites are 71 sites (16,40%), fourth place is the proceeding 40 titiles (9,24%), reports 13 titles (3%), theses 7 titles (1.62%), and neswpapers 3 titles (0.69%). For reference, 268 titles were use, namely books with 73 titles *27,24%(, journals with 172 titles (64.18%), proceedings with 12 titles (4,48%), and websites with 11 sites (4.10%).These, reports and foreing newspapaer are not used. The year of publication of the most rerefences wa in 2015-2017 which wa 41 titles (15.29%), in the second position in te 2012-2014 range, namely 40 titles (14.92%), and in the thirdposition was the 2018-2021 range, which was 39 titles, (14,55%). It was concluded tat domestic and foreign referenecea aamounted to 901 titles, anf journals were the most cited documents, followed by books and websites. Newspaper are the least cited documents.The most reference year ranges are 2018 – 2021, and the oldest references are documents published in <1970. Writers of Jurnal IPI are up to date because tjey use the lastest information, which is in the 2012-2021 range.